Formulation and evaluation of red ginger extract tablet (Zingiber officinale var. rubrum) as lozenges - Paramitha, Ratih; Marfitania, Taranipa; Januarti, Ria; Hanief, Said; Tambunan, Pravil Mistryanto (Jurnal Prima Medika Sains, 2024)
Red ginger (Zingiber officinale var. rubrum) with a high content of phenols (e.g. gingerol, shogaol, etc.) has potential effects against throat inflammation such as cold, sore throat, tonsilitis, etc. This research aims to determine the formulation of lozenge tablets using red ginger extracts. Lozenges tablets are made from dry ginger extract using a wet granulation method prepared by various concentrations of pregelatinized cassava starch 1 % w/v (F0); 2 % w/v (F1) and 5 % w/v (F2) as a binder and HPMC 2 % w/v (F3) as a comparative binder. Red ginger extract was prepared by maceration method using 96% ethanol solvent which is then evaporated using a rotary evaporator to obtain a thick extract. Thick red ginger extract is formulated into lozenges with various formulations F0, F1, F2, and F3. Physical characteristics evaluation of lozenge tablets includes physical appearance, weight uniformity, hardness, and disintegration time. The physical appearance of the tablet is round in shape and bright yellow in color. Based on the evaluation of all the formulas made, F2 has good criteria as a red ginger extract lozenge which has a hardness of 6 kg and disintegration time of 5 minutes 4 seconds.